EVALUASI SISTEM AKUNTANSI PEMBELIAN BAHAN BAKU PADA PT. LKD MULTI INDUSTRI - Ita Mustika; Khadijah Khadijah; Elvi Noviawati (JURNAL CAFETARIA, 2022)
Inventory of raw materials is the main element that needs to be considered in carrying out production activities. The limited amount of raw material inventory will hamper the smooth production process and will reduce customer confidence in the company. Inventory of raw materials has an important role in the production process. The use of raw materials must be in accordance with sales orders received from customers. The data analysis method used in this research is qualitative analysis with a descriptive approach. The term "raw materials" is closely related to companies engaged in manufacturing. This raw material is the main component in the production process of manufacturing companies. This main component must be maintained in terms of quality and quantity. For this reason, the company must have a good accounting system that involves a clear separation of functions, the use of adequate accounting documents and records, and procedures carried out by several sections. From the analysis and discussion of the accounting system for the purchase of raw materials at PT. Multi-Industry LKd, some advantages and disadvantages can be stated. In procuring raw materials, the company uses a raw material purchasing system, both in cash and on credit. The raw material purchasing system at PT Lkd Multi Industri is quite effective and in accordance with the company's Standard Operations and Procedures, as evidenced by the separation of functions, so that it is not carried out by only one function even though there are functions that concurrently have other functions. The documents and accounting records used are also quite good, although there are still things that need to be addressed.